Plasma Components and Platelet Activation Are Essential for the Antimicrobial Properties of Autologous Platelet-Rich Plasma: An In Vitro Study - Drago, Lorenzo; Bortolin, Monica; Vassena, Christian; Romanò, Carlo L.; Taschieri, Silvio; Fabbro, Massimo Del (PLOS ONE, 2014)
Autologous platelet concentrates are successfully adopted in a variety of medical fields to stimulate bone and soft tissue regeneration. The rationale for their use consists in the delivery of a wide range of platelet-derived bioactive molecules that promotes wound healing. In addition, antimicrobial properties of platelet concentrates have been pointed out. In this study, the effect of the platelet concentration, of the activation step and of the presence of plasmatic components on the antimicrobial activity of pure platelet-rich plasma was investigated against gram positive bacteria isolated from oral cavity. The antibacterial activity, evaluated as the minimum inhibitory concentration, was determined through the microdilution two-fold serial method. Results seem to suggest that the antimicrobial activity of platelet-rich plasma against Enterococcus faecalis, Streptococcus agalactiae, Streptococcus oralis and Staphylococcus aureus is sustained by a co-operation between plasma components and platelet-derived factors and that the activation of coagulation is a fundamental step. The findings of this study may have practical implications in the modality of application of platelet concentrates.